2007
DOI: 10.1038/sj.clpt.6100317
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin: Something Old, Something New, Sometimes Borrowed and Now Renewed

Abstract: The molecular target of rapamycin (mTOR) is central to a complex intracellular signaling pathway and is involved in diverse processes including cell growth and proliferation, angiogenesis, autophagy, and metabolism. Although sirolimus (rapamycin), the oldest inhibitor of mTOR, was discovered more than 30 years ago, renewed interest in this pathway is evident by the numerous rapalogs recently developed. These newer agents borrow from the structure of sirolimus and, although there are some pharmacokinetic differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
181
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(186 citation statements)
references
References 108 publications
1
181
0
4
Order By: Relevance
“…The effect of rapamycin on cell viability and autophagy of drug-sensitive and drug-resistant cells Rapamycin is a natural macrolide antibiotic that inhibits mTOR signaling and causes cell cycle arrest, and importantly, induces autophagy (Hartford and Ratain, 2007). We examined whether rapamycin affects cell death in Ras-NIH3T3 cells versus their drug-resistant counterpart.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of rapamycin on cell viability and autophagy of drug-sensitive and drug-resistant cells Rapamycin is a natural macrolide antibiotic that inhibits mTOR signaling and causes cell cycle arrest, and importantly, induces autophagy (Hartford and Ratain, 2007). We examined whether rapamycin affects cell death in Ras-NIH3T3 cells versus their drug-resistant counterpart.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical data suggest that mTOR inhibitors may induce tumor regression in some patients (Dancey, 2005;Panwalkar et al, 2004). Rapamycin (sirolimus), one of the main mTOR inhibitors used in clinical trials (Hartford and Ratain, 2007), has shown significant chemotherapeutic antitumor activity in various models (Kim et al, 2008;Weppler et al, 2007). Moreover, studies have established that rapamycin can downregulate and disable the P-glycoprotein pump (Pop et al, 2009) and enhance cellular drug uptake in cells overexpressing P-glycoprotein (Pawarode et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A large volume of distribution (approximately 12 L/kg) is seen with sirolimus, the majority of which is distributed into red blood cells (approximately 95%) [18, 30]. Sirolimus is mainly metabolized via hepatic CYP3A enzymes, is primarily excreted via the fecal route, has a clearance that ranges from 1.45 to 6.93 mL/min/kg), and a half-life of approximately 62 hours [18, 27]. …”
Section: Pharmacological Aspects Of Mtor Inhibitorsmentioning
confidence: 99%
“…Poorly soluble in water, sirolimus is given orally whereas temsirolimus is a water-soluble dihydroxymethyl propionic acid ester prodrug mainly used as an iv formulation. It quickly undergoes hydrolysis to sirolimus after iv administration, so that most of its clinical effects are likely attributable to the sirolimus metabolite [32].…”
Section: Novel Approved Np Drugs and Promising Clinical Candidatesmentioning
confidence: 99%